Cell Experiment Equipment by Using Ashes as Electrolytes: https://doi.org/10.69692/SUJMRD0901265 - VONGVILAY, Chanpheng; VANGCHANGYIA, Somsack; SOUADA, Paoxiong; CHOUALUEHER , Sivone; KEOMANICHAN, Phonepadith (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This article presents information about an experiment on how to create simple galvanic cell experiment equipment by using waste ash from burning as electrolytes, a copper plate as a cathode, and a zinc plate as an anode. The main purpose is to create a set of experimental equipment for teaching physics under the title of electrochemistry, to examine the possibility of generating electricity from ash, to study the change of the mixture ratio between the ashes and water that affects the open circuit voltage (OCV), to compare the value of the open circuit voltage from the sedimentation ashes electrolyte and non-sedimentation ashes electrolyte, and to study the pH value of the ash’s electrolyte within two hours. The research revealed that it can create five sets of galvanic cells by using different quantities of ashes, and it was found that the ashes from burning can generate electricity. The same type of ash with a different quantity will give almost the same OCV values, and changing the mixture ratio between ash and water will not affect the OCV values, which found that the mixing ratio between water and dry ash to become an electrolyte must use a minimum mixing ratio of water equal to ash or use a ratio of water more than ash to mix together. The results of measuring the value of OCV over a period of 2 hours found that the average value is almost constant, equal to 0.7 V. Here, we found that if the ash is allowed to settle, the value of OCV will decrease slightly, and if the ash is not allowed to settle, the value of OCV is constantly unchanged. It was also found that the pH value of the ash in each galvanic cell during the period of 2 hours was the same, with an average high alkalinity of about 13. This shows that alkaline electrolytes can generate electricity and have almost constant electricity. These five devices can be applied as a teaching tool for the Physics and Chemistry subject in the title of electrochemistry for students at the secondary school level and bachelor’s students because of an easy way to fabricate galvanic cells. The materials used are cheap and easy to find. It can also be used to study the characteristics of electrical conductivity in ash’s electrolyte and the characteristics of ash’s electrolyte.